RISK MITIGATION IN THE LAUSIMEME DAM CONSTRUCTION PROJECT - Untung Tri Uripto; Isfenti Sadalia; Nazaruddin (RADJA PUBLIKA, 2023)
The construction of the Simeme Dam is a part of efforts to support the development of the agricultural sector and to meet the needs of water in North Sumatra. The Lausimeme Dam construction project has been delayed from its planned schedule. The potential risks that will hinder the completion of the project when viewed from the internal, external and project sources and how to mitigate risks to obtain factors which influence the risk mitigation of the Lau Simeme Dam project in order to determine risk mitigation strategies. This study uses observation, interviews and field surveys compiled by a questionnaire based on a literature study that has been conducted on respondents related to the Lausimeme Dam Development Project and uses a causal descriptive method with a quantitative approach by identifying risks and risk indicators related to what possibilities may arise and will occur in the Lausimeme Dam Development Project. There are 77 risks that are relevant or likely to occur to the Lausimeme Dam Development Project and it is concluded that 68 risks are classified as high and 9 risks are classified as moderate in terms of influence level. Of the 68 risks that are classified as high, there are 15 top risks (largest ranking) that have the highest possibility to occur (probability) and the largest impact based on an assessment of the Lausimeme Dam construction project, therefore mitigation of these possible risks is needed. Mitigation that will be implemented to minimize the possibility of these risks to accour, including: socializing, fulfilling documents and licensing documents, obtaining BMKG data, involving the community and non-governmental organizations, making resource estimates based on analysis, carrying out cross-functional coordination, and preparing CAR.